ADB's second decade 1977-1986 updated edition. (Metro Manila, Philippines Asian Development Bank, 2017)
This second volume from the series ADB through the Decades shows how ADB responded to the growing diversity among its developing member countries as both membership and operations widened during 1977-1986.
Keywords: Public administration -- Developing countries..; Electronic books